Analisis Minat Beli Toko Kelontong Di Kecamatan Wonokromo, Surabaya Dengan Pendekatan Store Atmosphere - Deograsias Yoseph Y. F. (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2019)
The grocery store industry is still facing a form of economic business that hasgood prospects, even in a crisis. However, in the same period many took thegrocery that went bankrupt, because they were no longer able to maintain sales.There needs to be a fundamental change in the grocery store in order, but thegrocery store is starting to rise from behind. As Indonesian people, are we ready to help by diverting shopping at grocery stores. By agreeing to Store Atmosphere,it is expected that willingness to buy from grocery stores will increase.